Intravitreal Bevacizumab as anti-vascular endothelial growth factor in the management of complications of diabetic retinopathy - Arevalo, J. Fernando (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.